2003
DOI: 10.1002/pola.10675
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of 1,3‐dienes with functional groups. II. Free‐radical polymerization of N‐(2‐methylene‐3‐butenoyl)piperidine

Abstract: The free‐radical homopolymerization and copolymerization behavior of N‐(2‐methylene‐3‐butenoyl)piperidine was investigated. When the monomer was heated in bulk at 60 °C for 25 h without an initiator, about 30% of the monomer was consumed by the thermal polymerization and the Diels–Alder reaction. No such side reaction was observed when the polymerization was carried out in a benzene solution with 1 mol % 2,2′‐azobisisobutylonitrile (AIBN) as an initiator. The polymerization rate equation was found to be Rp ∝ [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…With the literature value of 128 kJ/mol for E d ,9 one can calculate E p − E t /2 as 20.1 kJ/mol. This value was smaller than that of PiA (25.5 kJ/mol),7 indicating that the R p of DEA was higher than that of PiA.…”
Section: Resultsmentioning
confidence: 67%
See 4 more Smart Citations
“…With the literature value of 128 kJ/mol for E d ,9 one can calculate E p − E t /2 as 20.1 kJ/mol. This value was smaller than that of PiA (25.5 kJ/mol),7 indicating that the R p of DEA was higher than that of PiA.…”
Section: Resultsmentioning
confidence: 67%
“…Through the study of diene polymerizations, the Diels—Alder dimerization and thermal polymerization are not favorable because they may increase the apparent rate of monomer consumption and make the analysis of the polymerization kinetics complicated. In a previous article,7 we reported that a PiA containing piperidine amide function either had a strong tendency to form the Diels—Alder dimer or to undergo thermal polymerization during the polymerization in bulk. Therefore, the possibility of such a side reaction was also examined in this study.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations